Monitoring scaling and dental calculus removal with an optical fluorescence system - Sivieri-Araujo, G. [UNESP]; Fontana, C. R. [UNESP]; Costa, M. M.; Rastelli, Alessandra Nara de Souza [UNESP]; Pereira, L. P. C.; Kurachi, C.; Bagnato, V. S. (Iop Publishing Ltd, 2014)
Fluorescence results from a process that occurs under certain conditions in molecules known as fluorophores, fluorochromes or fluorescent dyes when they absorb light. The molecule is excited to a higher energy state and emits fluorescent light. The emission wavelength is always higher than the excitation wavelength. Optical diagnoses by fluorescence can be used in medicine and dentistry. It does not cause injury to tissues because it is a noninvasive method and can add benefits to clinical treatments. The aim of this case report was to apply an optical fluorescence system for wide-field image viewing and visual monitoring of the management of plaque and dental calculus before and after periodontal scaling to improve the diagnoses and follow-up of patients with periodontal disease. The results suggest that it is possible to observe, with a fluorescence system, residual plaque and calculus that were not easily seen by the naked eye during oral inspection. Thus, the optical technique can potentially improve periodontal screening efforts, especially in patients undergoing periodontal maintenance.
Keywords: optical diagnosis; fluorescence; dental calculus; dental plaque; biofilm; dental scaling